Knowledge mobilization across boundaries with the use of novel organizational structures, conferencing strategies, and technological tools: The Ontario Consortium of Undergraduate Biology Educators (oCUBE) Model - Lovaye Kajiura; Julie Smit; Colin Montpetit; Tamara Kelly; Jennifer Waugh; Fiona Rawle; Julie Clark; Melody Neumann; Michelle French (Collected Essays on Learning and Teaching, 2014)
The Ontario Consortium of Undergraduate Biology Educators (oCUBE) bringstogether over 50 biology educators from 18 Ontario universities with the commongoal to improve the biology undergraduate experience for both students andeducators. This goal is achieved through an innovative mix of highlyinteractive face-to-face meetings, online conferencing platforms (wiki andvideo conferencing), monthly online newsletters, and other activities. The beautyof the oCUBE model is that it meshes with the active learning methods that itsmembers use in their own teaching. It also creates a community of practice withintra- and inter-institutional collaborations that assist in resolving educationalissues of both common and immediate importance to oCUBE members. oCUBE membersreport that oCUBE activities and resources are very effective in helping themlearn new teaching strategies and in developing professionally.